Psycho-Socio-Cultural Effects in Work towards Work Performance of Nurse - Putri P.A, Maria Prieska; Palupi, Retno; Purnomo, Windhu (International Journal of Psychosocial Rehabilitation, 2020)
Background: Not all nurses’ performance in Indonesia has a good performance. Nurse Performance in Panti Waluya Sawahan Hospital Malang, showed that 17.4% of nurses had sufficient performance, and 11.1% had poor nurse performance. Poor performance of the nursing process can reduce the quality of health services to clients resulting in decreased health status. Objective: This study aims to analyze the effect of Psycho-Socio-Cultural on the performance of the nurses’ process at Malang Panti Waluya Hospital. Method: This research is a quantitative study with a cross sectional design approach. The population in this study were all nurses in the inpatient room with simple random sampling technique. The research instrument used questionnaires and observation sheets. Results: The results showed that all variables had p values <0.001, with OR = 16.73 for Work Culture, OR = 8.14 for Work Environment, and OR = 5.11 for Psychological Factor variables. Conclusion: The results showed that psycho-socio-cultural in work affects the performance of the nursing process.